Persistence and non-stationarity in the built-up land footprint across 89 countries - Sakiru Adebola Solarin (Elsevier, 2021)
This paper deals with the analysis of the degree of persistence and non-stationarity in the built-up land footprint time series referring to 89 countries all over the world. Using long memory and fractional integration methods the results indicate the existence of positive trends in 57 of the countries examined, while 7 series display negative trends. Dealing with persistence we observe a large of degree of heterogeneity across countries, with some countries displaying short memory patterns, while others showing orders of integration significantly higher than 1.